2004
DOI: 10.1017/s1047951104005074
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis, management, and results of treatment for aortopulmonary window

Abstract: The aortopulmonary window is a communication between the ascending aorta and the pulmonary trunk in the presence of two separate arterial valves. This uncommon congenital anomaly is reported rarely in the literature. We present here our experience with 16 patients, emphasizing the importance of early closure of the defect by a transaortic approach. We performed surgery on 16 patients over a period of 13 years using a transaortic approach under cardiopulmonary bypass. The median age of the patients at the time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 14 publications
(12 reference statements)
0
8
0
2
Order By: Relevance
“…We preferred the transaortic approach in our cases because coronary orifices are visualised better and reconstruction of both arteries is safer by this technique; we did not experience any complications. Similarly, Mert et al (21) reported that they did not document residual defects when they preferred the transaortic approach. For the patch, we use either glutaraldehyde-treated autologous pericardium, or Gore-Tex of 0.4 mm thickness.…”
Section: Discussionmentioning
confidence: 98%
“…We preferred the transaortic approach in our cases because coronary orifices are visualised better and reconstruction of both arteries is safer by this technique; we did not experience any complications. Similarly, Mert et al (21) reported that they did not document residual defects when they preferred the transaortic approach. For the patch, we use either glutaraldehyde-treated autologous pericardium, or Gore-Tex of 0.4 mm thickness.…”
Section: Discussionmentioning
confidence: 98%
“…Since [9][10][11] , in contrast with our experience, where five patients (71.4%) underwent repair through the transpulmonary approach, 1 patient (14.2%) through the transaortic approach and in another case (14.2%), the closing was accomplished through dissection and repair.…”
Section: Tetralogy Of Fallot (1)mentioning
confidence: 99%
“…The closing through hemodynamic intervention is also reported for small defects and to close any residual defect 11,12 . According to Soares and cols., for this procedure, the type of APW must be characterized and it must be type I (proximal), of a small dimension (3 to 4 mm) and not associated with anomalous origin of the coronary arteries.…”
Section: Tetralogy Of Fallot (1)mentioning
confidence: 99%
“…Alternativ besteht die Mçglichkeit des transpulmonalen bzw. des transaortalen Zugangsweges[5,24], welcher aber das potenzielle Risiko eines Restshunts beinhaltet. In Einzelfällen ist bei kleinen drucktrennenden Defekten ein katheterinterventioneller Verschluss mçglich.…”
unclassified
“…Dies betrifft auch Restdefekte nach operativem Verschluss[25,26]. Assoziierte Herzfehler werden heutzutage in der Regel im Rahmen der Primäroperation korrigiert[5,24]. Die Prognose des operativ korrigierten aortopulmonalen Fensters ist bei frühzeitiger Diagnosestellung und bei Fehlen komplexer assoziierter Vitien exzellent, vergleichbar mit der Prognose beim Verschluss eines Ventrikelseptumdefektes [5].Unsere Ergebnisse zeigen, dass das aortopulmonale Fenster echokardiografisch zuverlässig diagnostiziert werden kann.…”
unclassified